Implementasi Sistem Informasi Penjualan Berbasis Web Untuk Meningkatkan Efisiensi Pengelolaan Data - Ginting, Jimmy; Romulo P. Aritonang; Sumarlin (JISTI: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2025)
The development of information technology encourages organizations and small and medium enterprises (SMEs) to utilize information systems to support operational activities. Manual sales data management often causes various problems such as reporting delays, recording errors, and difficulties in data retrieval. This study aims to design and implement a web-based sales information system that can improve the efficiency and accuracy of sales data management. The research method used is the waterfall method, which includes the stages of needs analysis, system design, implementation, and testing. The results show that the web-based sales information system can assist the process of recording transactions, managing product data, and generating sales reports quickly and accurately. Thus, this system is expected to support more effective management decision-making.